Coronavirus Impacts on Midwestern Row‐Crop Agriculture. Issue 1 (11th October 2020) - Schnitkey, Gary D.; Paulson, Nicholas D.; Irwin, Scott H.; Coppess, Jonathan; Sherrick, Bruce J.; Swanson, Krista J.; Zulauf, Carl R.; Hubbs, Todd
Abstract: Impacts from the coronavirus pandemic have depressed market returns to corn and soybean farmers in the Midwest, extending pressures that have existed since 2013 and worsened by trade disputes with China. Without large ad hoc federal aid, income on Midwestern grain farms would have been quite low and the ongoing cash flow crunch much worse. Farmland prices have not adjusted downward, in part due to continuing ad hoc federal aid, but also because interest rates have been historically very low. The financial (solvency) position of Midwestern grain farms is surprisingly strong because of the strength in land values. However, the financial condition of Midwestern row‐crop agriculture could deteriorate markedly if recent and large infusions of ad hoc federal aid dissipates or if interest rates rise sharply.